Bridging the gap: The transition of young emerging evaluators from theory to practice in South Africa’s M&E landscape - Matlala, Lesedi Senamele (Edelweiss Applied Science and Technology, 2025)
This study explores how South African universities can better prepare Young Emerging Evaluators (YEEs) for the transition from academic learning to professional Monitoring and Evaluation (M&E) practice. Despite the growing demand for skilled evaluators in government, NGOs, and the private sector, a persistent gap exists between theoretical training and real-world application. Using a qualitative, multi-method approach—comprising focus group discussions, semi-structured interviews, and document analysis—the study examines the adequacy of current academic curricula in equipping YEEs with the practical skills needed for evaluation work. Grounded in Experiential Learning Theory and Situated Learning Theory, the findings reveal that while universities provide strong theoretical foundations, they fall short in offering structured, field-based learning opportunities. YEEs often enter the workforce underprepared to manage stakeholder dynamics, resource constraints, and the political complexities of evaluation environments. Employers and practitioners similarly report that graduates lack applied competencies and critical soft skills. The study concludes that universities should embed work-integrated learning, mentorship, and professional exposure into M&E programs to strengthen workplace readiness. These reforms are essential for building sustainable internal evaluation capacity in South Africa and reducing dependence on post-graduation interventions, contributing to the professionalization and long-term growth of the M&E field.